2004
DOI: 10.3928/0191-3913-20040501-08
|View full text |Cite
|
Sign up to set email alerts
|

Use of Optical Coherence Tomography in Myopia

Abstract: Purpose: To measure retinal thickness and retinal nerve fiber layer thickness using optical coherence tomography in patients with myopia. Patients and Methods: Thirty patients (13 girls and 17 boys) 14 to 18 years old were included in the study. The control group consisted of 15 patients. Each patient was subjected to routine ophthalmic investigations, which included the assessment of visual acuity for near and distant objects, autorefractometry, measurement of intraocular pressure, biometry, and ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…The effects of refraction on RNFL thickness have been debated; some authors have found no difference (Mrugacz et al. 2004) and others have described thinning of the RNFL with greater negative refraction (Choi & Lee 2006; Huynh et al.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of refraction on RNFL thickness have been debated; some authors have found no difference (Mrugacz et al. 2004) and others have described thinning of the RNFL with greater negative refraction (Choi & Lee 2006; Huynh et al.…”
Section: Discussionmentioning
confidence: 99%
“…A general thinning of the inner and outer macular area was also detected in the children with albinism, but not in the three children with aniridia. An association between reduced macular thickness and myopia has been described (Mrugacz et al. 2004; Pierre‐Kahn et al.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have been carried out on normal eyes in children. Mrugacz et al. (2004) examined 15 normal children aged 12–18 years, Altintas et al.…”
Section: Discussionmentioning
confidence: 99%
“…However, when evaluating retinal abnormalities assessed with OCT in children, it would be more appropriate to compare findings with normal values in children. Only a few studies have reported normal macular thickness in children (Mrugacz et al. 2004; Shields et al.…”
Section: Introductionmentioning
confidence: 99%